Pembingkaian Berita Pada Media Lokal (Analisis Framing Pemberitaan Calon Bupati Malang Pada Harian Radar Malang Tanggal 1-7 Oktober 2015) - Rahadi, Rahadi (ARISTO, 2017)
This research were focused on the news in the newspapers Radar Malang, about construction news regent and deputy regent candidate Malang October 1-7, 2015. There were three candidates for the election of the Regent and Vice Regent 2015-202 period, namely: the candidate regent Malang; (1) Nurcholis Muhammad Mufid of independent elements, (2) Renda Krishna and M Sanusi of coalition Madep Manteb Mantep (PKB, NasDem, Golkar, Gerindra, Democrat), (3) Dewanti Rumpoko and Masrifah Hadi from PDIP. Researchers used the theory of hierarchy levels to understand, how the framing of information on the three pairs of candidates. In this study, researchers used the analytical model and the framing of Zhongdang Pan Geraald Konsicki. The model uses four structural framing is Syntactically, Scripts, Thematic and Rhetoric.Based on study results, the news displayed by Radar Malang less balanced. This is evident from the Renda Krishna as the incumbent is given the space and the number of reports that more than any other potential mates. And their special news column titled Coming 5 Years Madep Manteb. Plus on the first page is kept up Radar Malang given space to direct the reader linked to column 5 Years Ahead Madep Manteb along with the headline raised. Associated with the theory of hierarchy levels, from internal factors, namely the level of the organizational level, and the level of media routines is clear that extremely pro Radar Malang Renda Krishna. This is evidenced by the news that tends to be positive.